Effects of pre-primary education on cognitive and affective learning outcomes among primary school children in Nigeria (2005)
The study sought to investigate the effects of pre-primary education on the cognitive and effective learning outcomes among primary school children in Nigeria. Three hundred and twenty primary one pupils selected from ten equivalent schools in both rural and urban locations participated. These cut across those who attended and those who did not attend preprimary schools; male and female puf0, am pupils in rural and urban schools. Data collection involved the use of Cognitive Skill Tests (CST) and Attitude to School Questionnaire (ASQ). A 2x2x2 analysis of variance (ANOVA), and graphical illustrations were used to analyse the data. The results show that those who were exposed to preprimary education performed significantly better in literary and numeracy tests as well as exhibited better attitude to schooling than those who did not. The implications of the findings were discussed with a view to improving the following aspects of pre-primary education in Nigeria: access, enrolment, classroom practice, and teacher training/in-service programmme.